2022
DOI: 10.3390/pollutants2030019
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the National Pollutant Release Inventory as a Policy Tool to Curb Atmospheric Industrial Emissions in Canada

Abstract: To curb greenhouse gas emissions and reduce atmospheric pollutants in Canada, many pieces of environment legislation are targeted at reducing industrial emissions. Traditional regulation prescribes penalties through fines to discourage industries from polluting, but, in the past two decades, alternative forms of environmental regulation, such as the National Pollutant Release Inventory (NPRI), have been introduced. NPRI is an information management tool which requires industries to self-report emissions data b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Интенсификация хозяйственной деятельности оказывает усиливающееся влияние не только на составляющие радиационного баланса системы атмосфера-поверхность Земли, но и приводит к возрастающему поступлению в атмосферу загрязняющих веществ в виде химических соединений и взвешенных частиц техногенного происхождения (49,50). Они представляют собой аэрозоли -либо концентрированные растворы, либо твердые частицы, находящиеся в атмосфере во взвешенном состоянии.…”
Section: доля лет с аномальным количеством июльских осадков в периоды...unclassified
“…Интенсификация хозяйственной деятельности оказывает усиливающееся влияние не только на составляющие радиационного баланса системы атмосфера-поверхность Земли, но и приводит к возрастающему поступлению в атмосферу загрязняющих веществ в виде химических соединений и взвешенных частиц техногенного происхождения (49,50). Они представляют собой аэрозоли -либо концентрированные растворы, либо твердые частицы, находящиеся в атмосфере во взвешенном состоянии.…”
Section: доля лет с аномальным количеством июльских осадков в периоды...unclassified
“…For example, a study found higher levels of benzene, toluene, ethylbenzene, and xylene in rural areas compared with cities due to different point sources such as domestic coal combustion during winter. 53 We did not make use of point sources because in Canada, it is based on industry-reported data, and these emissions from point sources are known to underestimate emissions 54 and, to our knowledge, there is no emission inventory specific to the Montreal area that includes all relevant sources.…”
Section: Strengths and Limitationsmentioning
confidence: 99%